METODE PENGASUHAN ANAK PASANGAN PERNIKAHAN DINI (STUDI KASUS TIGA KELUARGA PERNIKAHAN DINI DI KECAMATAN PONJONG KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA) - Siti Rofingah (UIN Sunan Kalijaga Yogyakarta, 2019)
Abstract This research was conducted with the aim of describing the childcare methods carried out by three early marriage families in Ponjong District, Gunungkidul Regency. The background of this research is the existence of government policy in Law Number 1 of 1974 article 7 paragraph (1) concerning Marriage which explains the minimum age limit for marriage so that the benefit of the household is achieved, but the phenomenon of early marriage is still happening in the District of Ponjong Regency Gunungkidul, even able to maintain the household and be able to carry out childcare duties at a young age if reviewed psychologically immature mentally, emotionally, psychologically and physically. This type of research is a qualitative research with a type of case study research (field research). Determination of informants by purposive sampling. The subjects of this study were three families of early marriage, children of early marriage partners (if they were able to provide information) and the Young Clerk of the Wonosari Religious Court Law. Then, the object of research is the method of parenting early marriage partners. Data collection techniques used were observation, interviews, and documentation. While the data analysis techniques used are data reduction, data presentation and conclusion making. The results showed that the methods carried out by early marriage couples included exemplary education methods, methods through habituation, education methods through advice and dialogue, as well as education methods through the awarding and punishment. The three early marriage families apply a number of collaborative methods for parenting. Keywords: childcare methods, early marriage.